Review of Splendours of the Subcontinent: A Prince's Tour of India 1875-76 - Beth Hunt (Janeway JS, 2018)
A review of the exhibition Splendours of the Subcontinent: A Prince's Tour of India 1875-76, 11 March 2017 – 18 June 2017 at the Cartwright Gallery, Bradford.